Solitary central neurofibroma of the maxilla: A Case Report - Danesteh, Hossein; Sadeghzade, Azita; Jafarpour, Dana (Brazilian Dental Science, 2020)
Neurofibroma is a benign tumor which rarely occurs in the oral cavity. Generally, oral neurofibroma is part of a neurofibromatosis type-1 like syndrome (Von Recklinghausen’s disease) and rarely occurs as a solitary lesion of oral cavity. Up to now, few cases have been reported with the solitary neurofibromas of tongue and submandibular gland. The tumor can also be rarely located centrally in the bone. This research presents a central neurofibroma case in the maxillary bone which has no relationship with the neurofibromatosis.KeywordsCentral neurofibroma; Neurofibromatosis; Solitary neurofibroma; Von Recklinghausen’s disease.